2009
DOI: 10.1074/jbc.m806605200
|View full text |Cite
|
Sign up to set email alerts
|

Calprotectin S100A9 Calcium-binding Loops I and II Are Essential for Keratinocyte Resistance to Bacterial Invasion

Abstract: Epithelial cells expressing calprotectin, a heterodimer of S100A8 and S100A9 proteins, are more resistant to bacterial invasion. To determine structural motifs that affect resistance to bacterial invasion, mutations were constructed in S100A9 targeting the calcium-binding loops I and II (E36Q, E78Q, E36Q,E78Q) and the C terminus (S100A9 1-99 and S100A9 1-112 ), which contains putative antimicrobial zinc-binding and phosphorylation sites. The S100A8 and mutated S100A9 encoding plasmids were transfected into cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
69
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(74 citation statements)
references
References 58 publications
4
69
0
1
Order By: Relevance
“…Furthermore, the proteins bind arachidonic acid, and depletion of arachidonic acid has also been suggested as a mechanism of bacterial growth inhibition (49,50). Observations suggesting that S100A8/A9 contributes to mucosal innate immunity are that the complex inhibits invasion of epithelial cells by bacterial pathogens (51), and a recent study showing that S100A9 is crucial for keratinocyte resistance to invasion by Listeria monocytogenes and Salmonella typhimurium (52). In the present study, we provide evidence for another and more direct antibacterial mechanism.…”
Section: Discussionsupporting
confidence: 70%
“…Furthermore, the proteins bind arachidonic acid, and depletion of arachidonic acid has also been suggested as a mechanism of bacterial growth inhibition (49,50). Observations suggesting that S100A8/A9 contributes to mucosal innate immunity are that the complex inhibits invasion of epithelial cells by bacterial pathogens (51), and a recent study showing that S100A9 is crucial for keratinocyte resistance to invasion by Listeria monocytogenes and Salmonella typhimurium (52). In the present study, we provide evidence for another and more direct antibacterial mechanism.…”
Section: Discussionsupporting
confidence: 70%
“…Calprotectin is a heterodimeric complex of calcium-binding proteins S100A8 (MRP8 or calgranulin A; 10.8 kDa) and S100A9 (MRP14 or calgranulin B; 13.2 kDa) (6). S100A8 and S100A9 are members of the S100 family of proteins (17).…”
mentioning
confidence: 99%
“…S100 family members are characterized by their two EF-hand calcium-binding motifs; these proteins are involved in cell growth, cell differentiation, cell cycle progression, cell survival, protein phosphorylation, transcription, cancer development, and inflammatory diseases (18). Calprotectin shows broad-spectrum antimicrobial activity against Candida albicans and bacteria, including Capnocytophaga sputigena, Escherichia coli, Staphylococcus epidermidis, Listeria monocytogenes, S. Typhimurium, and Porphyromonas gingivalis (4,6,(19)(20)(21). After stable transfection to express the calprotectin complex, an epithelial cell line (KB) showed increased resistance to invasion by Listeria monocytogenes and Salmonella enterica serovar Typhimurium (6).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous study (21), a significantly higher absolute number of neutrophils was found in BALF samples of the pneumonia group than in the α-Defensins and S100A proteins in BALF Articles nonpneumonia group, but the BALF samples were collected in most cases on the 5th d of life, whereas the samples were all collected in this study within the first 48 h of life. S100A8 and S100A9 proteins form the heterodimer calprotectin, with demonstrated antimicrobial activity against numerous microorganisms, particularly fungi (26,(29)(30)(31)(32)). However, when tested alone, neither S100A8 nor S100A9 showed activity in the Candida growth assay (31).…”
Section: Discussionmentioning
confidence: 99%